Thyroxine binding globulin excess detected by neonatal screening - Jin, Hye Young (Ann Pediatr Endocrinol Metab, 2016)
Inherited thyroxine binding globulin (TBG) disorder can be identified incidentally or through neonatal screening test. TBG excess is characterized by high levels of thyroxine (T4) but normal level of free T4 (fT4), while TBG deficiency presents with low T4 levels and normal fT4 levels. A 27-day-old newborn was brought to the hospital because of hyperthyroxinemia detected by neonatal screening. His T4 level was 18.83 µg/dL (normal range, 5.9–16.0 µg/dL). His mother had no history of any thyroid disease. His fT4 and thyroid stimulating hormone (TSH) levels were 1.99 ng/dL (normal range, 0.8–2.1 ng/dL) and 4.54 mIU/L (normal range, 0.5–6.5 mIU/L), respectively. His serum total triiodothyronine (T3) level was 322.5 ng/dL (normal range, 105.0–245.0 ng/dL). His TBG level was 68.27 mg/L (normal range, 16.0–36.0 mg/L) at the age of 3 months. At 6 months and 12 months of age, his TBG levels were 48.77 mg/L (normal range, 16.0–36.0 mg/L) and 50.20 mg/L (normal range, 14.0–28.0 mg/L), respectively, which were 2 to 3 times higher than normal values. Hormonal studies showed consistently elevated T3 and T4 levels and upper normal levels of fT4 and free T3 with normal TSH levels. His growth and development were normal. TBG excess should be considered as a potential differential diagnosis for hyperthyroxinemia and especially high T3 levels with normal TSH concentration.